COLEOPTERA AS BIOINDICATORS AND PEST COMPLEXES IN ARID AGROECOSYSTEMS OF KARAKALPAKSTAN: A LITERATURE-BASED SYNTHESIS FOR SUSTAINABLE AGRICULTURE (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Coleoptera are among the most diverse insect orders and include taxa that are simultaneously useful bioindicators, natural enemies, decomposers and harmful phytophages. In Karakalpakstan and the wider Southern Aral Sea region, aridification, salinization, irrigation transformation and expansion of shelterbelts increase the need for systematic monitoring of beetle assemblages. This paper synthesizes published data on ground beetles, darkling beetles, blister beetles, longhorn beetles and host-plant pest complexes from Karakalpakstan and adjacent Northwestern Uzbekistan. Published records indicate 104 species and subspecies of Carabidae in northwestern landscapes, 79 Tenebrionidae in western Uzbekistan, and 27 Meloidae in the Southern Aral Sea region. The most species-rich Carabidae landscape was the Kyzylkum desert, while agrocenoses also retained high recorded richness. The synthesis proposes a practical monitoring framework combining pitfall traps, light traps, host-plant inspection and seasonal surveys to support integrated pest management and biodiversity conservation in arid agroecosystems.
Keywords: Coleoptera; Karakalpakstan; Southern Aral Sea; Carabidae; Tenebrionidae; Cerambycidae; agroecosystems; biodiversity monitoring; integrated pest management.